The Effect of Atorvastatin in Knee Osteoarthritis - Eman Mohammed Jasim (Institute of Medico-legal Publications Pvt Ltd, 2021)
The aim of this, randomized, double-blind, placebo-controlled study is to evaluate the effect of using 40mg atorvastatin on the progression of joint structural changes and symptoms over 3months in Iraqi patients with symptomatic knee osteoarthritis.This study was performed at Department of Rheumatology, Baghdad Teaching Hospital during the period from September 2020 to January 2021.A total of 44 patients with knee osteoarthritis were assigned to the placebo group (n=21) and atorvastatin group (n=23)that was received atorvastatin 40mg once daily. Both groups received etoricoxib tablets 60mg as a rescue medicine on need. Both groups were treated continuously for 12 weeks.Serum levels of C-terminal telopeptide of type II collagen CTXII, high sensitive c-reactive protein HS-CRP and Western Ontario and McMaster Universities Osteoarthritis Index WOMAC was measured before and after three months of treatment.Resultsshowed that after three months of treatment, the atorvastatin group showeda significant symptomatic improvement in total WOMAC scoring (P<0.0001) associated with a significant reduction (P<0.001) in serum CTXII, HS-CRP level.These results confirmed that the atorvastatin treatment in patients with knee osteoarthritis has clinical efficacy in reducing symptoms through the improvement of WOMAC index and reduction of serum level of CTXII and HS-CRP. In conclusions: Atorvastatin in a dose of 40mg daily can reduce the symptoms of OA.